Desenvolvimento e morfoanatomia dos frutos de Attalea microcarpa Mart. (Arecaceae - Arecoideae) - (:unkn) unknown (Universidade Federal do Amazonas, 2012)
Palms have a great relevance into Amazon ecosystem, to understand the relationships between palms and environment we describe the morphoanatomical aspects of the development of the fruits of Attalea microcarpa Mart at Private Reserve of Natural Heritage Sítio Bons Amigos, BR-174, ramal DNER, Km 15, Manaus, AM.. The Attalea microcarpa s fruit development takes 280 days, started with spathe and finish with fruit dispersal. The staminate flower has three sepals, three petals, 9-15 stamens and a vestigial gynoecium. The pistillate flower is just like a young fruit, with three petals and three sepals, gynoecium syncarpous with short stylus and trifurcated stigma, superior ovary, tricarpellate, trilocular, containing one egg in each locule. It presents four levels of tissue organization in cross section, these being distinguished by the position of the vascular bundles. The gynoecium reacted to lipid content, mucilages and pectin. The fruit is a fibrous drupe, epicarp simple, tortuous and the cuticle its cover of epicuticular waxes form reddish indumentum. The mesocarp has three distinct layers, first near the epidermis composed of fibrous bundles which differentiate into fibrovascular bundles as the fruit ripens. The second mesocarp layer is completely parenchymatous and have reserved of starch grains and lipids. The layer is composed of many fibrovascular bundles that divides the fleshy mesocarp of the endocarp. The endocarp in young fruit is soft and gelatinous, passing through a process of centrifugal and basipetal hardening. The seed begins to form shortly after fertilization, at 40 days it is possible to visualize the formation of the tegument, which will adhere to the endocarp forming pyren. The endosperm remains in core until about 80 days when it is already possible to see the early formation of the walls and from 140 days its solid. The endosperm reserves are composed primarily of lipid compounds. The characteristics of Attalea microcarpa morphoanatomic associated with the biological aspects of the plant are of important relevance to understanding the taxonomy and plant interactions in the environments in which it occurs, and generate support for further studies on the diversity of the group.
Keywords: Attalea microcarpa; Morfoanatomia; Produtividade; Desenvolvimento; Attalea microcarpa; Morphoanatomic; Productive; Development; Palmeira; CIÊNCIAS BIOLÓGICAS